Nuclear Reactor Thermal Hydraulics and Other Applications - Post Guillen, Donna (IntechOpen, 2013)
This book includes contributions from researchers around the world on numerical developments and applications to predict fluid flow and heat transfer, with an emphasis on thermal hydraulics computational fluid dynamics. Our ability to simulate larger problems with greater fidelity has vastly expanded over the past decade. The collection of material presented in this book augments the ever-increasing body of knowledge concerning the important topic of thermal hydraulics. Featured topics include coolant channel analysis, thermal hydraulic transport and mixing, as well as hydrodynamics and heat transfer processes. The contents of this book will interest researchers, scientists, engineers and graduate students.